Small diameter vascular grafts incorporating zinc coordination units in situ and methods of making
Patent Information
- Application Number
- CN202611497519.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-24
- Publication Date
- 2026-10-30
AI Technical Summary
然而,锑属于潜在毒性重金属元素,采用Sb2O3催化所得PET中通常残留有数十至数百ppm的锑元素,在长期体内植入场景下,锑离子可通过酯键水解、材料降解及物理扩散等途径缓慢释放至周围组织,存在慢性蓄积毒性及潜在致癌风险
(1)本发明采用原位缩聚法,ZnTPA配位单元以化学键形式均匀分散并锚定于聚酯基体中,克服了物理共混方式中无机填料团聚、分散不均匀、力学性能劣化等缺陷,同时避免了表面涂层法存在的涂层脱落失效风险,具有长期服役稳定性;
Smart Images

Figure CN122998475A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of vascular graft technology, and in particular to a small-diameter vascular graft with in situ introduced zinc coordination units and its preparation method. Background Technology
[0002] Coronary artery bypass grafting and peripheral vascular reconstruction are standard surgical interventions for treating severe arterial occlusive disease, and their successful implementation highly depends on suitable vascular replacement materials. Polyethylene terephthalate (PET) and expanded polytetrafluoroethylene (ePTFE) are commonly used synthetic vascular grafts in clinical practice, demonstrating acceptable long-term patency rates in the clinical replacement of large-diameter (>6 mm) arteries. However, in small-diameter (<6 mm) applications, the long-term failure rate of these materials is significantly higher, mainly attributed to postoperative infection, acute thrombosis, and restenosis caused by intimal hyperplasia. The material basis for this lies in the bioinert nature of the PET and ePTFE surfaces, which lack the ability to actively regulate host cell behavior and are unable to support endothelial cell adhesion and tissue regeneration. Therefore, developing small-diameter grafts with both good blood compatibility and rapid endothelialization capabilities has become an urgent technical challenge.
[0003] Besides thrombosis and restenosis, bacterial infection also poses a serious threat to the long-term function of vascular grafts. These complications involve the interaction of multiple biological processes, including coagulation, infection, and tissue proliferation, making a single strategy insufficient to address them comprehensively. Current efforts to improve the performance of small-diameter grafts mainly include biomimetic structural design (such as electrospinning to construct extracellular matrix-like scaffolds) and the introduction of bioactive substances, aiming to achieve synergistic regulation of physical cues and biochemical signals. Regarding the selection of bioactive components, inorganic metal ions such as Zn... 2+ Cu 2+ Co 2+ and Ag + These have been proven to have varying degrees of antibacterial activity. Among them, zinc ions (Zn) 2+ It has attracted much attention due to its broad-spectrum antibacterial properties, endothelial activity-promoting effects, and platelet function-regulating effects.
[0004] Existing technologies mostly use physical blending to introduce zinc compounds into the polymer matrix. This method has obvious drawbacks such as poor dispersibility and deterioration of the mechanical properties of composite materials, making it difficult to meet the comprehensive performance requirements of small-diameter vascular grafts.
[0005] Meanwhile, the industrial production of medical-grade polyethylene terephthalate (PET) currently mostly uses antimony-based (such as antimony trioxide Sb₂O₃), titanium-based, or tin-based heavy metal compounds as polycondensation catalysts. Among them, antimony-based catalysts are the most widely used due to their high catalytic activity and low cost. However, antimony is a potentially toxic heavy metal element. PET produced using Sb₂O₃ catalysis usually contains tens to hundreds of ppm of antimony. In long-term implantation scenarios, antimony ions can be slowly released into surrounding tissues through ester bond hydrolysis, material degradation, and physical diffusion, posing a risk of chronic cumulative toxicity and potential carcinogenicity. Although titanium-based catalysts have relatively low toxicity, their catalytic activity is sensitive to trace amounts of moisture, making polymerization process control difficult, and some titanium compounds may induce oxidative stress reactions in vivo; tin-based catalysts also have certain controversies regarding cytotoxicity. These heavy metal catalyst residue issues fundamentally restrict the safety of PET as a substrate for long-term implantable medical devices.
[0006] Furthermore, in the traditional PET polymerization route, the catalytic function and the antibacterial / bioactive function are separated. The catalyst loses its value after the polycondensation reaction is completed. If the graft is to be endowed with antibacterial or endothelialization-promoting functions, additional antibacterial components (such as silver-based or copper-based inorganic fillers or organic antibacterial agents) need to be introduced, which brings a series of problems such as filler agglomeration, mechanical degradation and additional toxicological evaluation burden.
[0007] Therefore, how to achieve the biofunctionalization of the PET matrix itself without introducing heavy metal catalyst residues is a long-standing but unresolved technical problem in this field. Summary of the Invention
[0008] The purpose of this invention is to provide a small-diameter vascular graft with in-situ introduced zinc coordination units and its preparation method. Zinc oxide (ZnO) completely replaces the traditional heavy metal polycondensation catalyst, and chemically anchored ZnTPA coordination units are generated in-situ during the polymerization process, resulting in a small-diameter vascular graft with excellent mechanical properties, blood compatibility, antibacterial activity and intrinsic biosafety.
[0009] To achieve the above objectives, the present invention provides a method for preparing a small-diameter vascular graft with in situ introduced zinc coordination units, comprising the following steps: S1. Add nano zinc oxide (ZnO) powder to ethylene glycol (EG), and then disperse it by ultrasonication and mechanical stirring to obtain a uniformly dispersed ZnO / EG suspension. S2. Terephthalic acid (PTA) is added to the ZnO / EG suspension in S1, and esterification and polycondensation reactions are carried out sequentially to obtain PET / ZnTPA material. S3. Dissolve the PET / ZnTPA material from S2 in hexafluoroisopropanol and stir magnetically until completely dissolved to obtain an electrospinning solution. S4. Inject the electrospinning solution of S3 into a syringe, and use a stainless steel rod rotating around its own central axis as a receiver to perform electrospinning to obtain a tubular body of nanofibers. After vacuum drying, a small-diameter blood vessel graft is obtained.
[0010] Preferably, in S1, the solid-liquid ratio of nano zinc oxide powder to ethylene glycol is 1.88-5.65 g: 150 mL, the ultrasonic dispersion power is 400-600 W, the time is 20-40 min, and the mechanical stirring time is 8-16 h.
[0011] Preferably, in S2, the solid-liquid ratio of terephthalic acid to ethylene glycol is 300~360g:150mL.
[0012] Preferably, in S2, the esterification reaction is carried out under a nitrogen atmosphere and a pressure of 0.2~0.4MPa, at a reaction temperature of 250~270℃, for a reaction time of 2~3h, and with a stirring speed of 80~120r / min.
[0013] Preferably, in S2, the polycondensation reaction is carried out at 270~290℃ and a vacuum degree <20Pa for 1.5~2.2h.
[0014] Preferably, in S3, the magnetic stirring time is 10~14h; the concentration of the electrospinning solution is 12~18%w / v.
[0015] Preferably, in S4, the electrospinning voltage is 16~20kV, the receiving distance is 13~17cm, and the solution propulsion speed is 1~1.5mL / h; the vacuum drying temperature is 35~40℃, and the time is 40~56h.
[0016] The present invention also provides a small-diameter vascular graft with in-situ introduced zinc coordination units, which is prepared by the above-mentioned method for preparing a small-diameter vascular graft with in-situ introduced zinc coordination units. It includes a tubular body of nanofibers, wherein the nanofibers are composed of polyethylene terephthalate with in-situ introduced zinc coordination units, the zinc coordination units being ZnTPA, and the zinc coordination units being uniformly dispersed in polyethylene terephthalate in a chemically anchored form.
[0017] Preferably, the inner diameter of the tubular body is 2.0 mm, and the diameter of the nanofibers in the tubular body is 0.3~1.5 μm.
[0018] Preferably, the ZnTPA content in small-diameter vascular grafts is 0.5~1.5wt%.
[0019] Therefore, the present invention, employing the above-mentioned method for in-situ introduction of zinc coordination units into a small-diameter vascular graft, has the following beneficial effects: (1) The present invention adopts in-situ polycondensation method, in which ZnTPA coordination units are uniformly dispersed and anchored in polyester matrix in the form of chemical bonds, overcoming the defects of inorganic filler agglomeration, uneven dispersion and mechanical property deterioration in physical blending method, while avoiding the risk of coating peeling failure in surface coating method, and has long-term service stability. (2) The PET / ZnTPA electrospun vascular grafts obtained by the present invention maintain the complete polyester main chain structure, have good spinnability and uniform fiber morphology; the introduction of ZnTPA coordination units significantly improves the mechanical properties of the material, and the tensile strength, elongation at break and Young's modulus are all effectively enhanced, with the elongation at break exceeding 150%, and all mechanical indicators meet the clinical requirements for small-diameter vascular grafts; at the same time, they also have good blood compatibility (significantly reduced blood cell adhesion, hemolysis rate far below the 5% safety threshold specified by ISO 10993-4) and excellent inherent antibacterial activity (antibacterial rates against Escherichia coli and Staphylococcus aureus can reach 99.15% and 96.66%, respectively), and the antibacterial function originates from the matrix itself, does not depend on surface coatings or physical additives, and the performance is durable and stable.
[0020] (3) In this invention, zinc oxide (ZnO) completely replaces traditional heavy metal polycondensation catalysts such as antimony trioxide (Sb2O3). The PET / ZnTPA material obtained by polymerization does not contain residual heavy metals such as antimony and tin that may be potentially toxic. This eliminates the safety hazards of chronic release and accumulation of heavy metal ions in the body under long-term implantation scenarios. At the same time, ZnO is converted in situ into chemically anchored ZnTPA coordination units during the catalytic polycondensation reaction. After completing the polymerization mission, the catalyst is transformed into the active functional component of the material, overcoming the disadvantages of traditional catalysts and antibacterial components being separated from each other and requiring additional compounding.
[0021] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0022] Figure 1 This is a combined diagram of the chemical structure characterization spectra of PET / ZnTPA1.0 in Example 2 of this invention and PET in Comparative Example 1. Figure 1 (a) in the middle is 1 H NMR spectrum Figure 1 (b) in the middle is 13 C NMR spectrum Figure 1 (c) in the image is the XRD diffraction pattern. Figure 1 (d) in the image represents the FTIR spectrum; Figure 2 These are schematic diagrams of the macroscopic morphology and SEM images of the microstructure of the vascular grafts in Examples 1-3 and Comparative Example 1 of the present invention; Figure 2 In the diagram, 'a' represents a schematic representation of the macroscopic morphology. Figure 2 In the image, b represents the SEM image of the microstructure. Figure 3 This is a schematic diagram of the resilience performance of the PET / ZnTPA1.0 vascular graft obtained in Example 2 of the present invention. Figure 3 (a) in the figure is a schematic diagram of a PET / ZnTPA1.0 vascular graft. Figure 3 (b) in the diagram is a schematic diagram of the initial state of the PET / ZnTPA1.0 vascular graft. Figure 3 (c) in the diagram is a schematic diagram of the compression state of the PET / ZnTPA1.0 vascular graft. Figure 3 (d) in the figure is a schematic diagram of the recovery status of the PET / ZnTPA1.0 vascular graft; Figure 4 These are schematic diagrams illustrating the mechanical properties of the vascular grafts of Embodiments 1-3 and Comparative Example 1 of the present invention; Figure 4 (a) in the figure is a schematic diagram of the stress-strain curve. Figure 4 (b) in the diagram is a schematic diagram of the ultimate tensile strength. Figure 4 (c) in the diagram is a schematic diagram of the elongation at break. Figure 4 (d) in the figure is a schematic diagram of Young's modulus; Figure 5 These are macroscopic morphology and SEM images of blood cell adhesion on the surface of vascular grafts with different ZnTPA contents after incubation with whole blood in Examples 1-3 and Comparative Example 1 of this invention. Figure 5 (a) in the figure is a macroscopic morphology diagram. Figure 5 (b) in the image is a SEM image; Figure 6 These are schematic diagrams illustrating quantitative measurements of hematopoietic cell adhesion, blood compatibility, and water contact angle of vascular grafts with different ZnTPA contents in Examples 1-3 and Comparative Example 1 of the present invention. Figure 6 (a) in the diagram is a schematic diagram of blood cell adhesion density. Figure 6 (b) in the diagram is a schematic diagram of blood cell surface coverage. Figure 6 (c) in the diagram is a schematic diagram of the hemolysis rate. Figure 6 (d) in the diagram is a schematic representation of the water contact angle; Figure 7 These are schematic photographs of antibacterial plates after co-culturing vascular grafts with different ZnTPA contents in Examples 1-3 and the comparative example of the present invention. Figure 7 Image (a) is a schematic diagram of an E. coli plate after co-culture. Figure 7 (b) is a schematic diagram of a Staphylococcus aureus plate after co-culture; Figure 8 This is a schematic diagram illustrating the quantitative analysis of the antibacterial rate of vascular grafts with different ZnTPA contents in Examples 1-3 and Comparative Example 1 of the present invention. Figure 8(a) in the diagram is a schematic diagram of the antibacterial rate against Escherichia coli. Figure 8 (b) in the diagram is a schematic diagram of the antibacterial rate against Staphylococcus aureus.
[0023] Figure 9 These are SEM images of bacteria under normal, unco-cultured conditions and bacteria after co-culturing with PET / ZnTPA1.5 according to the present invention. Figure 9 In the image, 'a' represents a SEM image of normal, unco-cultured E. coli. Figure 9 In the image, b is a SEM image of E. coli after co-culturing with PET / ZnTPA1.5. Figure 9 In the image, 'c' represents a SEM image of normal, unco-cultured Staphylococcus aureus. Figure 9 In the image, d represents the SEM image of Staphylococcus aureus after co-culturing with PET / ZnTPA1.5. Detailed Implementation
[0024] This invention provides a method for preparing small-diameter vascular grafts with in situ introduced zinc coordination units, comprising the following steps: S1. Add nano zinc oxide powder to ethylene glycol, and then disperse it by ultrasonication and mechanical stirring to obtain a uniformly dispersed ZnO / EG suspension. S2. Terephthalic acid is added to the ZnO / EG suspension in S1, and esterification and polycondensation reactions are carried out sequentially to obtain PET / ZnTPA material. S3. Dissolve the PET / ZnTPA material from S2 in hexafluoroisopropanol and stir magnetically until completely dissolved to obtain an electrospinning solution. S4. Inject the electrospinning solution of S3 into a syringe, and use a stainless steel rod rotating around its own central axis as a receiver to perform electrospinning to obtain a tubular body of nanofibers. After vacuum drying, a small-diameter blood vessel graft is obtained.
[0025] In the in-situ polycondensation of terephthalic acid and ethylene glycol of this invention, ZnO simultaneously serves as a catalyst and zinc source. By controlling the amount of ZnO added, sufficient zinc is provided to convert into the desired amount of ZnTPA coordination units while catalyzing the polycondensation reaction. Simultaneously, by pre-dispersing ZnO in ethylene glycol to form a ZnO / EG suspension before mixing it with terephthalic acid for polymerization, it is ensured that ZnO participates uniformly in the reaction from the initial stage of polymerization, rather than being physically blended after polymerization. Under the synergistic effect of the above-mentioned addition amount and order, ZnO is in-situ converted into uniformly dispersed and chemically anchored ZnTPA coordination units in the polyester matrix during the esterification and polycondensation reactions of terephthalic acid and ethylene glycol. This avoids the inherent risks of filler agglomeration and the residue and migration of heavy metal catalysts in the product, common in physical blends. The zinc species are stably anchored in the polymer matrix rather than physically blended, maintaining mechanical integrity and electrospinning processability. In situ introduction of zinc via metal-carboxylate coordination can transform bioinert PET into an inherently bioactive material that can simultaneously address thrombosis and bacterial infection without relying on surface coatings or physical additives that could impair long-term performance, making it suitable for small-diameter vascular grafts.
[0026] Preferably, in step S1, the solid-liquid ratio of nano-zinc oxide powder to ethylene glycol is 1.88-5.65 g: 150 mL, the ultrasonic dispersion power is 400-600 W, and the time is 20-40 min; the mechanical stirring time is 8-16 h. This invention controls the solid-liquid ratio of nano-zinc oxide powder to ethylene glycol within the above range, ensuring that the product molecular weight meets the standard and that there is no nanoparticle agglomeration.
[0027] Preferably, in S2, the solid-liquid ratio of terephthalic acid to ethylene glycol is 300-360 g: 150 mL. By controlling the solid-liquid ratio of terephthalic acid to ethylene glycol within the above range, this invention ensures the esterification reaction proceeds fully, resulting in a polyester product with a suitable molecular weight.
[0028] Preferably, in S2, the esterification reaction is carried out under a nitrogen atmosphere and a pressure of 0.2~0.4MPa, at a reaction temperature of 250~270℃, for a reaction time of 1.5~2.5h, and with a stirring speed of 80~120r / min.
[0029] In a more preferred embodiment, the esterification reaction produces water, and the esterification reaction is considered complete when the theoretical amount of water is removed.
[0030] Preferably, in S2, the polycondensation reaction is carried out at 270~290℃ and a vacuum degree <20Pa for 1.5~2.2h.
[0031] In a more preferred embodiment, the initial polycondensation stage of the polycondensation reaction lasts for 40-50 minutes, and the final polycondensation stage lasts for 60-80 minutes.
[0032] Preferably, in S3, the magnetic stirring time is 10~14h; the concentration of the electrospinning solution is 12~18%w / v.
[0033] Preferably, in step S4, the electrospinning voltage is 16-20 kV, the receiving distance is 13-17 cm, and the solution propulsion speed is 1-1.5 mL / h; the vacuum drying temperature is 35-40 °C, and the time is 40-56 h. This invention stabilizes the nanofiber structure by removing the solvent through vacuum drying.
[0034] Preferably, the stainless steel rod has a diameter of 2 mm. Nanofibers are wound around the outside of the stainless steel rod by electrospinning to form a tubular body.
[0035] The present invention also provides a small-diameter vascular graft with in-situ introduced zinc coordination units, which is prepared by the above-mentioned method for preparing a small-diameter vascular graft with in-situ introduced zinc coordination units. It includes a tubular body of nanofibers, wherein the nanofibers are composed of polyethylene terephthalate with in-situ introduced zinc coordination units, the zinc coordination units being ZnTPA, and the zinc coordination units being uniformly dispersed in polyethylene terephthalate in a chemically anchored form.
[0036] Preferably, the inner diameter of the tubular body is 2 mm, and the diameter of the nanofibers in the tubular body is 0.3~1.5 μm.
[0037] Preferably, the ZnTPA content in the small-diameter vascular graft is 0.5~1.5 wt%. This invention achieves excellent antibacterial activity and blood compatibility while maintaining good mechanical properties and spinnability by controlling the ZnTPA content within the above range.
[0038] The present invention will be further described below with reference to the accompanying drawings and embodiments. Unless otherwise defined, the technical or scientific terms used in this invention should be understood in their ordinary sense by those skilled in the art. The features mentioned above or in the specific examples mentioned in this invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the invention and are not intended to limit the scope of the invention.
[0039] Example 1 This invention provides a small-diameter vascular graft with in-situ introduced zinc coordination units, comprising a tubular body of nanofibers. The nanofibers are composed of polyethylene terephthalate (PET) with in-situ introduced ZnTPA, and the ZnTPA is uniformly dispersed in the PET in a chemically anchored form. The inner diameter of the tubular body is 2.0 mm, and the diameter of the nanofibers in the tubular body is in the range of 0.3~1.5 μm. The ZnTPA content in the small-diameter vascular graft is 0.5 wt%. The preparation method includes the following steps: S1. Add 1.88g of nano zinc oxide powder to 150mL of ethylene glycol and mix in a 1L glass beaker. Disperse ultrasonically at 540W for 30min and mechanically stir for 12h to obtain a uniformly dispersed ZnO / EG suspension.
[0040] S2. Add 330g of terephthalic acid to the ZnO / EG suspension in S1, and transfer it to a 1L multi-functional polymerization reactor. Esterification is carried out under a nitrogen atmosphere and a pressure of 0.3MPa at 260℃ for 2 hours, with a stirring speed of 100r / min. Water is generated during esterification; the reaction is considered complete when 70mL of the theoretical water volume is removed. Maintaining the stirring speed, a polycondensation reaction is then carried out at 280℃ under a vacuum of <20Pa. The initial polycondensation stage lasts 45min, and the final polycondensation stage lasts 75min. The reaction is terminated when the stirring reaches the preset torque value, yielding PET / ZnTPA material.
[0041] S3. Dissolve the PET / ZnTPA material from S2 in hexafluoroisopropanol and stir magnetically for 12 hours to ensure complete dissolution, resulting in an electrospinning solution with a concentration of 15% w / v.
[0042] S4. Inject the electrospinning solution from S3 into a 10mL syringe. Using a stainless steel rod (2.0mm in diameter) rotating around its own central axis as a receiver, electrospinning is performed at room temperature and 40% relative humidity. The electrospinning voltage is 18kV, the receiving distance is 15cm, and the solution propulsion speed is 1mL / h. A tubular body of nanofibers is obtained. The tubular body of nanofibers is placed in an oven and vacuum dried at 37℃ for 48h to obtain a small-diameter vascular graft, denoted as PET / ZnTPA0.5.
[0043] Example 2 This invention provides a small-diameter vascular graft with in-situ introduced zinc coordination units, wherein the mass percentage of ZnTPA in the small-diameter vascular graft is 1.0 wt%. In preparation method S1, the amount of nano zinc oxide powder added is 3.76 g, and the rest is the same as in Example 1, denoted as PET / ZnTPA1.0.
[0044] Example 3 This invention provides a small-diameter vascular graft with in-situ introduced zinc coordination units, wherein the mass percentage of ZnTPA in the small-diameter vascular graft is 1.5 wt%. In preparation method S1, the amount of nano zinc oxide powder added is 5.65 g, and the rest is the same as in Example 1, denoted as PET / ZnTPA1.5.
[0045] Comparative Example 1 A vascular graft, differing from Example 1 in that the tubular body of the nanofibers does not contain ZnTPA. Its preparation method differs from Example 1 in that S1 is omitted; 330g of terephthalic acid is directly added to 150mL of ethylene glycol, followed by the addition of 400ppm of tetrabutyl titanate as a catalyst; the remaining steps are the same as S2-S4 of Example 1, yielding the vascular graft, denoted as PET.
[0046] Performance testing The performance of PET / ZnTPA electrospun vascular grafts with different ZnTPA contents (0wt%, 0.5wt%, 1.0wt%, 1.5wt%) prepared in Examples 1-3 and Comparative Example 1 was tested, and the test methods are as follows.
[0047] I. Characterization Experiment (1) Structural characterization: The obtained vascular grafts PET / ZnTPA1.0 and PET were characterized by nuclear magnetic resonance spectroscopy. 1 HNMR, 13 C NMR characterization, Figure 1 (a) 1 The H NMR results showed a singlet at δ=8.1ppm, which was attributed to the aromatic ring proton in the terephthalic acid structural unit; and a singlet at δ=4.8ppm, which was attributed to the methylene proton in the ethylene glycol structural unit. Figure 1 (b) 13 C NMR results showed that PET / ZnTPAx exhibited a characteristic peak of ester carbonyl at 165.5 ppm, and the chemical shift of the aromatic carbon was consistent with that of pure PET, indicating that PET was generated by in-situ polymerization in Example 2 of this invention, and the polyester backbone remained intact after the introduction of ZnTPA without changing its basic structure. Figure 1 The XRD characterization results in (c) show that the characteristic diffraction peaks of the ZnO precursor at 2θ = 31.8°, 34.4°, 36.3°, 47.5° and 56.6° completely disappeared after polymerization, while new diffraction peaks appeared at 2θ = 12.1°, 16.9° and 24.9°. These peak positions are consistent with the standard diffraction pattern of zinc terephthalate (ZnTPA), confirming that ZnO has been converted into ZnTPA coordination units in situ rather than existing in a physically embedded form. Figure 1 The (d) FTIR spectrum in the image shows that PET / ZnTPA1.0 at 1716 cm⁻¹ -1 (C=O stretching vibration of ester carbonyl group), 1261 cm -1 (COC asymmetric and symmetric stretching vibrations) and 726 cm -1 The characteristic absorption band at the (para-substituted benzene ring out-of-plane bending vibration) site is consistent with that of pure PET, further confirming that the chemical structure of the polyester backbone was not affected by the introduction of zinc species.
[0048] (2) Microscopic morphology: The macroscopic morphology of the vascular grafts was directly photographed using a digital camera, and the morphology and microstructure of the vascular grafts were observed using a scanning electron microscope at an accelerating voltage of 1.0 kV. The results are as follows: Figure 2 As shown.
[0049] Figure 2 Image 'a' shows a well-defined tubular graft with a uniform outer diameter of approximately 3 mm and an intact, continuous wall structure; [The image shows a vascular graft constructed from...] Figure 2 As shown in b, the vascular graft exhibits a highly porous nonwoven fiber structure with fiber diameters ranging from 0.3 to 1.5 μm. The fiber surface is smooth, and no micron-sized particle aggregation or phase separation was observed, indicating that the ZnTPA coordination units are uniformly dispersed in the polyester matrix and have good spinnability.
[0050] (3) Resilience Test: A 3cm long PET / ZnTPA1.0 electrospun tubular graft was cut and subjected to radial compression with tweezers until it collapsed completely. The graft was then unloaded, and its morphological recovery was observed and recorded. Photos were taken with a digital camera at the initial state, the compressed state, and the unloaded recovery state. Good resilience was defined as the graft recovering to near its original shape after unloading, without significant permanent deformation or structural damage. Results are as follows: Figure 3 As shown, PET / ZnTPA1.0 electrospun tubular grafts collapse under compression but spring back to near their original shape once unloaded, reflecting good elasticity. This property is beneficial for intraoperative suturing and manipulation and helps maintain lumen patency under physiological loads.
[0051] (4) Mechanical property testing: Mechanical properties were tested using a universal tensile testing machine at a tensile rate of 20 mm / min and a sample length of 3 cm. Figure 4 As shown.
[0052] Figure 4 (a) shows the typical nonlinear tensile behavior of electrospun fibers, characterized by an initial linear elastic region, a subsequent nonlinear plateau region, and strain hardening before fracture. All electrospun vascular grafts of the present invention have an elongation at break of more than 150%, indicating that they have sufficient flexibility to accommodate pulsatile blood flow. Figure 4 (b) Figure 4 (c) and Figure 4Figure (d) shows that the ultimate tensile strength at fracture exhibits a content-related increase, rising from 5.51 ± 0.32 MPa in pure PET to 7.90 ± 0.89 MPa in PET containing 1.0 wt% ZnTPA, and reaching 9.10 ± 0.36 MPa with 1.5 wt% ZnTPA. Young's modulus gradually increased from 47.47 ± 1.44 MPa (0 wt%) to 82.99 ± 6.51 MPa (1.5 wt%), indicating that the introduction of ZnTPA coordination units effectively improved the stiffness of the polymer matrix by enhancing intermolecular interactions and chain rigidity. Simultaneously, the elongation at break increased significantly with increasing ZnTPA content, rising from 175.21 ± 5.61% (0 wt%) to 251.18 ± 17.59% (1.5 wt%), confirming that the introduction of ZnTPA enhanced strength without sacrificing ductility, and instead improved the flexibility and compliance of the graft.
[0053] In summary, these results demonstrate that in situ introduction of ZnTPA into the PET matrix modulates the mechanical properties of electrospun vascular grafts. PET / ZnTPA1.0 exhibits a good balance between tensile strength, modulus, and ductility in all tests, with its mechanical properties falling within the range suitable for small-diameter vascular graft applications, while maintaining the excellent resilience demonstrated by compression-recovery tests.
[0054] II. In vitro blood compatibility Fresh anticoagulated rabbit blood was collected, and the same batch of blood samples was used for the following blood cell adhesion experiment and hemolysis experiment.
[0055] (1) Blood cell adhesion experiment: PET / ZnTPA electrospun vascular grafts with different ZnTPA contents were cut into fibrous membranes (1cm × 1cm). The fibrous membranes were incubated with 200μL of the above-mentioned anticoagulated rabbit blood (whole blood) at 37℃ for 1h. After rinsing with PBS, the samples were fixed with 2.5% glutaraldehyde for 4h, dehydrated with a series of ethanol gradients (50, 75, 90, and 100 vol%), and then vacuum dried. Macroscopic morphology images of the fibrous membranes were photographed using a digital camera, and the adhesion of platelets and erythrocytes on the surface of the fibrous membranes was observed using a scanning electron microscope (SEM). The results are as follows: Figure 5 As shown in the figure. Quantitative analysis was performed on the SEM images of the fiber membrane, and the results are as follows. Figure 6 As shown.
[0056] Depend on Figure 5 It can be seen that the surface of pure PET vascular grafts is densely covered with adherent blood cells, while the surface of PET / ZnTPA-containing vascular grafts has fewer adherent blood cells, indicating that the introduction of ZnTPA can reduce blood cell adhesion. Figure 6 (a) in Figure 6As shown in (b), compared with the pure PET vascular graft control, all PET / ZnTPA vascular grafts significantly reduced hematopoietic cell adhesion, with PET / ZnTPA0.5 exhibiting the strongest reduction effect: adhesion density and surface coverage decreased to 45.52±5.48% and 37.75±5.06% of the PET control, respectively (PET / ZnTPA1.0: 58.21±7.99% and 59.28±14.11%, PET / ZnTPA1.5: 59.20±7.06% and 69.19±10.72%). This indicates that the introduction of ZnTPA in this invention can effectively reduce hematopoietic cell adhesion.
[0057] (2) Hemolysis test: Take the same anticoagulated rabbit blood as described above, dilute it with physiological saline, and prepare a 2.5% (v / v) red blood cell suspension. Cut PET / ZnTPA electrospun vascular grafts with different ZnTPA contents into fibrous membranes (1cm×1cm), and place them into test tubes. Add 2mL of diluted red blood cell suspension to each tube. Use red blood cells without fibrous membranes and diluted with physiological saline as a negative control, and use red blood cells without fibrous membranes and diluted with deionized water as a positive control. After gently mixing, incubate all samples at 37℃ for 1h. Then remove the fibrous membranes and centrifuge the remaining suspension at 2000rpm for 10min. Measure the absorbance of the supernatant at 545nm using an ELISA reader. The hemolysis percentage is calculated according to the following formula: In the formula, , and The absorbance values represent the absorbance of the sample, negative control group, and positive control group, respectively. The results are as follows: Figure 6 As shown. By Figure 6 As shown in (c), the hemolysis rate of all vascular grafts of the present invention is far below the internationally recognized safety threshold of 5% (ISO 10993-4) (indicated by dashed lines). When the ZnTPA content is 0, 0.5, 1.0, and 1.5 wt%, the hemolysis rates are measured to be 1.69 ± 0.37%, 0.91 ± 0.15%, 0.60 ± 0.31%, and 1.03 ± 0.08%, respectively. This indicates that the vascular grafts prepared by the present invention have good blood compatibility and will not cause destructive hemolysis of the erythrocyte membrane.
[0058] (3) Water contact angle test: The water contact angle (WCA) of PET / ZnTPA electrospun fiber membranes with different ZnTPA contents was measured using an optical contact angle meter. The results are as follows: Figure 6 As shown. By Figure 6As shown in (d), the water contact angle of the pure PET vascular graft is 139.48°±0.81°, indicating hydrophobicity. With increasing ZnTPA content, the contact angle gradually decreases, with the contact angles of vascular grafts containing 0.5wt%, 1.0wt%, and 1.5wt% ZnTPA decreasing to 137.98°±0.18°, 132.08°±1.56°, and 127.95°±0.08°, respectively. This indicates that the introduction of ZnTPA coordination units with carboxylic acid groups can effectively improve surface hydrophilicity, which corroborates the results of reduced blood cell adhesion and enhanced blood compatibility in PET / ZnTPA grafts.
[0059] In summary, these results demonstrate that in situ introduction of ZnTPA into the PET matrix significantly enhances the blood compatibility of electrospun vascular grafts. The significant reduction in blood cell adhesion and surface coverage, coupled with hemolysis rates remaining below the 5% safety threshold in all groups, indicates that PET / ZnTPA grafts possess a favorable blood contact interface.
[0060] III. Antibacterial Activity The antibacterial activity of PET / ZnTPA electrospun vascular grafts with different ZnTPA contents against Gram-negative bacteria (Escherichia coli) and Gram-positive bacteria (Staphylococcus aureus) was evaluated using the plating method. PET / ZnTPA electrospun vascular grafts with different ZnTPA contents were cut into fibrous membranes (1 cm × 1 cm) and sterilized under ultraviolet light for 30 min to ensure aseptic conditions. Diluted bacterial suspensions (100 μL, 1 × 10⁻⁶ μL) were then used to evaluate the antibacterial activity against Gram-negative bacteria (E. coli) and Gram-positive bacteria (S. aureus). 6 CFU / mL was added to 24-well plates and co-cultured with nanofiber membranes. After a 100-fold dilution, 50 μL of the bacterial suspension was spread in triplicate onto fresh LB agar plates and incubated at 37°C for 18 h. Antibacterial activity was quantified by counting colony-forming units. A bacterial suspension in pure phosphate-buffered saline (PBS) was used as a control group. The antibacterial rate was calculated using the following formula: Antibacterial rate (%) = (AB) / A × 100%; In the formula, A represents the total number of colonies in the pure PBS control group, and B represents the total number of colonies in the experimental group.
[0061] The antibacterial plates after co-culture were photographed using a digital camera, and the results are as follows: Figure 7 As shown, a large number of bacterial colonies were observed on the pure PET vascular graft control group, while the number of colonies on the ZnTPA-containing vascular graft was significantly reduced. Furthermore, the antibacterial properties against Escherichia coli and Staphylococcus aureus were correspondingly improved with the increase of ZnTPA concentration.
[0062] Quantitative analysis of the antibacterial rates against Escherichia coli and Staphylococcus aureus was performed, and the results are shown in [Figure number missing]. Figure 8 ,like Figure 8 As shown in (a), the antibacterial rate against *E. coli* was 5.88% for pure PET vascular grafts, and increased to 71.22%, 97.02%, and 99.15% for grafts containing 0.5 wt%, 1.0 wt%, and 1.5 wt% ZnTPA, respectively. Figure 8 As shown in (b), the antibacterial rate against Staphylococcus aureus was 4.81% for pure PET vascular grafts, and increased to 53.83%, 94.75% and 96.66% for vascular grafts containing 0.5 wt%, 1.0 wt%, and 1.5 wt% ZnTPA, respectively.
[0063] Normal, unco-cultured *E. coli* and *S. aureus*, and *E. coli* and *S. aureus* co-cultured with PET / ZnTPA1.5 vascular grafts, were observed using scanning electron microscopy (SEM). Figure 9 As shown, normal unco-cultured Escherichia coli and Staphylococcus aureus have intact and smooth cell membranes. However, after co-culturing with PET / ZnTPA1.5 vascular grafts, Escherichia coli and Staphylococcus aureus exhibit distorted, collapsed, and broken morphologies, indicating that the cells are severely damaged.
[0064] In summary, these results indicate that PET / ZnTPA electrospun vascular grafts possess inherent antibacterial activity, which can be attributed to the Zn in the ZnTPA coordination units within the polymer matrix. 2+ It can exert a broad-spectrum bactericidal effect by disrupting the integrity of bacterial cell membranes and interfering with bacterial energy metabolism. Moreover, its antibacterial function originates from the matrix itself and does not depend on surface coatings or physical additives, thus exhibiting long-lasting stability.
[0065] IV. Intrinsic Viscosity Test The intrinsic viscosity of Examples 1-3 and Comparative Example 1 was tested using an Ubbelohde viscometer with an inner diameter of 0.88 mm. 0.125 g ± 0.001 g of sample was weighed and dissolved in 25 mL of phenol / tetrachloroethylene (mass ratio 3:2). The Ubbelohde viscometer was placed in a 25°C constant temperature water bath, and the prepared solution was added to the viscometer. The solvent outflow time t0 was recorded. The above operation was repeated to test the outflow time t of solutions with different ZnTPA contents, and the intrinsic viscosity was calculated according to the following formula: c : The concentration of the prepared solution is 5 mg / mL in this case; Relative viscosity =t / t0. The test was conducted three times, and the average value was taken. The results are shown in Table 1.
[0066] Table 1. Intrinsic viscosity of PET / ZnTPA with different ZnTPA contents
[0067] Table 1 shows that the intrinsic viscosity of PET / ZnTPA obtained by in-situ catalysis with ZnO gradually increases with increasing ZnTPA content. The intrinsic viscosity of PET / ZnTPA1.5 containing 1.5 wt% ZnTPA reaches 0.734 dL / g, which is significantly higher than that of PET obtained by traditional titanium-based catalysis (0.608 dL / g). These results indicate that ZnO can effectively catalyze the polycondensation reaction of terephthalic acid and ethylene glycol, resulting in a polymer with a high molecular weight. Furthermore, the introduction of ZnTPA coordination units does not inhibit the polymerization reaction; on the contrary, it helps to improve the intrinsic viscosity of the product. Higher intrinsic viscosity is beneficial for ensuring the mechanical properties of the electrospun fiber membrane, consistent with the trend of increasing tensile strength and elongation at break of PET / ZnTPA grafts with increasing ZnTPA content in the mechanical property test results.
[0068] Therefore, this invention employs the aforementioned method for in-situ introduction of zinc coordination units into small-diameter vascular grafts and their preparation. By completely replacing traditional heavy metal polycondensation catalysts with zinc oxide (ZnO), the polymerization process is made antimony-free, eliminating the risk of chronic release and in vivo accumulation of heavy metals such as antimony in long-term implantation scenarios. At the same time, the biological functions of zinc empower the PET matrix, giving the material excellent mechanical properties, blood compatibility, and broad-spectrum antibacterial activity, providing a solution for small-diameter vascular grafts that combines inherent biosafety and multifunctionality.
[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. A method for preparing a small-diameter vascular graft with in situ introduced zinc coordination units, characterized in that: Includes the following steps: S1. Add nano zinc oxide powder to ethylene glycol, and then disperse it by ultrasonication and mechanical stirring to obtain a uniformly dispersed ZnO / EG suspension. S2. Terephthalic acid is added to the ZnO / EG suspension in S1, and esterification and polycondensation reactions are carried out sequentially to obtain PET / ZnTPA material. S3. Dissolve the PET / ZnTPA material from S2 in hexafluoroisopropanol and stir magnetically until completely dissolved to obtain an electrospinning solution. S4. Inject the electrospinning solution of S3 into a syringe, and use a stainless steel rod rotating around its own central axis as a receiver to perform electrospinning to obtain a tubular body of nanofibers. After vacuum drying, a small-diameter blood vessel graft is obtained.
2. The method for preparing a small-diameter vascular graft with in-situ introduced zinc coordination units according to claim 1, characterized in that: In S1, the solid-liquid ratio of nano zinc oxide powder to ethylene glycol is 1.88-5.65 g: 150 mL, the ultrasonic dispersion power is 400-600 W, the time is 20-40 min, and the mechanical stirring time is 8-16 h.
3. The method for preparing a small-diameter vascular graft with in-situ introduced zinc coordination units according to claim 1, characterized in that: In S2, the solid-liquid ratio of terephthalic acid to ethylene glycol is 300~360g:150mL.
4. The method for preparing a small-diameter vascular graft with in-situ introduced zinc coordination units according to claim 1, characterized in that: In S2, the esterification reaction is carried out under a nitrogen atmosphere and a pressure of 0.2~0.4MPa, at a reaction temperature of 250~270℃, for a reaction time of 2~3h, and with a stirring speed of 80~120r / min.
5. The method for preparing a small-diameter vascular graft with in-situ introduced zinc coordination units according to claim 1, characterized in that: In S2, the polycondensation reaction is carried out at 270~290℃ and a vacuum degree <20Pa for 1.5~2.2h.
6. The method for preparing a small-diameter vascular graft with in-situ introduced zinc coordination units according to claim 1, characterized in that: In S3, the magnetic stirring time is 10~14h; the concentration of the electrospinning solution is 12~18%w / v.
7. The method for preparing a small-diameter vascular graft with in-situ introduced zinc coordination units according to claim 1, characterized in that: In S4, the electrospinning voltage is 16~20kV, the receiving distance is 13~17cm, and the solution propulsion speed is 1~1.5mL / h; the vacuum drying temperature is 35~40℃, and the time is 40~56h.
8. A small-diameter vascular graft with in situ introduced zinc coordination units, characterized in that: The small-diameter vascular graft prepared by any one of claims 1-7, comprising a tubular body of nanofibers, wherein the nanofibers are composed of polyethylene terephthalate with zinc coordination units introduced in situ, the zinc coordination unit being ZnTPA, and the zinc coordination units being uniformly dispersed in polyethylene terephthalate in a chemically anchored manner.
9. A small-diameter vascular graft for in situ introduction of zinc coordination units according to claim 8, characterized in that: The tubular body has an inner diameter of 2.0 mm, and the nanofibers in the tubular body have a diameter of 0.3~1.5 μm.
10. A small-diameter vascular graft for in situ introduction of zinc coordination units according to claim 8, characterized in that: The ZnTPA content in small-diameter vascular grafts is 0.5~1.5 wt%.
